9(x+8)+6=8(x+8)+4

Simple and best practice solution for 9(x+8)+6=8(x+8)+4 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 9(x+8)+6=8(x+8)+4 equation:


Simplifying
9(x + 8) + 6 = 8(x + 8) + 4

Reorder the terms:
9(8 + x) + 6 = 8(x + 8) + 4
(8 * 9 + x * 9) + 6 = 8(x + 8) + 4
(72 + 9x) + 6 = 8(x + 8) + 4

Reorder the terms:
72 + 6 + 9x = 8(x + 8) + 4

Combine like terms: 72 + 6 = 78
78 + 9x = 8(x + 8) + 4

Reorder the terms:
78 + 9x = 8(8 + x) + 4
78 + 9x = (8 * 8 + x * 8) + 4
78 + 9x = (64 + 8x) + 4

Reorder the terms:
78 + 9x = 64 + 4 + 8x

Combine like terms: 64 + 4 = 68
78 + 9x = 68 + 8x

Solving
78 + 9x = 68 + 8x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-8x' to each side of the equation.
78 + 9x + -8x = 68 + 8x + -8x

Combine like terms: 9x + -8x = 1x
78 + 1x = 68 + 8x + -8x

Combine like terms: 8x + -8x = 0
78 + 1x = 68 + 0
78 + 1x = 68

Add '-78' to each side of the equation.
78 + -78 + 1x = 68 + -78

Combine like terms: 78 + -78 = 0
0 + 1x = 68 + -78
1x = 68 + -78

Combine like terms: 68 + -78 = -10
1x = -10

Divide each side by '1'.
x = -10

Simplifying
x = -10

See similar equations:

| -8.4=-6g | | 0.3x=-4.5 | | 3+0.15=2x+0.30 | | 5(x+6)=4(x+7) | | 3(x-2)+2(x+1)=-14 | | 6(5x+7)=28x-70 | | 14x-21=3(4x-11) | | 3b-2=43 | | 13x+13=5x-11 | | home= | | 4(3x+2)=32 | | home=9 | | 5x-2456748=-44 | | -(3x+7)+6x=29 | | 4(2x+1)=27+3(2x-5) | | 5x-2(x-3)=30 | | 4y-1=19 | | 2(3x-5)=-40 | | -10x-3-2.5x+20=67 | | 4(6x-9)=156 | | 3(7x+5)+4=40 | | 4y-14+3y=28 | | 12x-15=69 | | 2(3x+4)-12=20 | | -16y+14+8y=6y+24 | | -3(6-2x)=12 | | 3(c-2)=15 | | 5x+7-4x=6 | | 7.2+4x=19.2 | | 6-x+12=10x+7 | | 36x^2-16=0 | | 3x-6x+2=-4x |

Equations solver categories